IMPLEMENTASI MONITORING PARAMETER LOCALIZER BERBASIS INTERNET OF THINGS - Afandi Sahputra; Mutiara Widasari Sitopu; Eriansyah Saputra Hasibuan; Donna Nurhaida Masdiana Sirait (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2021)
Abstract: In this study, one of the 4.0 industrial technologies was used to monitor the parameters of the localizer using an android based internet of things application to simplify and shorten the time for monitoring instrument landing system (ILS) equipment. Technicians, management of the Public Company (Perum) Indonesian Aviation Navigation Service Organizing Agency, and the Navigation Inspector do not have to go the runway to check the performance of the landing system instrument, simply use the android application to monitor the parameters of the localizer instrument. In the experiment, measuring the input voltage to the Arduino pin with a negative ground position and positive in the A9 pin position with the playing condition o Tx1 in the on position using a multimeter, the voltage value is 2.99 volt, while the main position on Tx1 is in the off condition, the voltage value is obtained 4.88 volts.       Keywords: instrument landing system; internet of things  Abstrak: Pada penelitian ini digunakan salah satu teknologi industri 4.0 untuk memonitoring parameter dari Localizer menggunakan aplikasi android berbasis Internet of Things (IoT) untuk mempermudah dan mempersingkat waktu dalam monitoring peralatan instrument landing system (ILS). Teknisi, manajemen Perusahaan Umum (Perum) Lembaga Penyelenggara Pelayanan Navigasi Penerbangan Indonesia LPPNPI dan Inspektur Navigasi tidak harus ke landasan pacu untuk mengecek kinerja instrument landing system cukup menggunakan aplikasi android untuk memonitoring parameter Localizer instrument landing system (ILS). Pada percobaan pengukuran tegangan input ke pin arduino dengan negatif pada posisi ground dan positif berada pada posisi pin A9 dengan kondisi main di TX1 pada posisi on dengan menggunakan multimeter didapat nilai tegangan 2,99 Volt, sedangkan posisi main di TX1 pada kondisi off didapat nilai tegangan 4,88 Volt. Kata kunci: instrument landing system; internet of things